2022
DOI: 10.1002/eco.2428
|View full text |Cite
|
Sign up to set email alerts
|

Green roof irrigation management based on substrate water potential assures water saving without affecting plant physiological performance

Abstract: Irrigation management in extensive green roofs (EGRs) is crucial in Mediterranean and semi‐arid climates, as it should guarantee efficient water use while ensuring plant survival and vegetation cover. However, benefits of maintaining moderately low substrate water potential (Ψs) have not been adequately investigated to date. An irrigation control unit based on Ψs thresholds for irrigation (MediWater Safe [MWS]) was compared to a common irrigation timer maintaining Ψs ⁓ 0 MPa (CTR) in shrub‐vegetated Mediterran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Heat stress is one of the challenges on GRs that influences the root that alters the water use efficiency as well as plant survival. The root vulnerability to heat stress is discussed by Savi et al ( 2016 ) and Tomasella et al ( 2022 ). While the crucial role of this trait is one of the main determinants of GRs performance, more investigations into this issue are recommended.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Heat stress is one of the challenges on GRs that influences the root that alters the water use efficiency as well as plant survival. The root vulnerability to heat stress is discussed by Savi et al ( 2016 ) and Tomasella et al ( 2022 ). While the crucial role of this trait is one of the main determinants of GRs performance, more investigations into this issue are recommended.…”
Section: Resultsmentioning
confidence: 99%
“…When sufficient irrigation has been delivered or in the case of rainfall, the irrigation system is prevented from running a cycle so there will be no excessive watering and superfluous supply. This method was applied by Tomasella et al ( 2022 ) on shrub vegetated Mediterranean extensive GRs, and results suggested that maintaining substrate water level at a certain threshold was significantly effective in optimizing GR benefits, reducing water consumption and favoring plant establishment. Besides, significant water savings were reported compared to the common irrigation timer maintenance method.…”
Section: Resultsmentioning
confidence: 99%